The Rey Auditory Verbal Learning Test: normative data for the Brazilian population and analysis of the influence of demographic variables - Magalhães,Sabrina S (2010)
The Rey Auditory Verbal Learning Test (RAVLT) is an efficient neuropsychological instrument for testing episodic declarative memory. Performance on this test can be influenced by demographic and cultural variables. The objective of the present study was to analyze the influence of demographics variables, such as age, gender, and education, on RAVLT performance in young and elderly adults. A Portuguese version of the RAVLT was administered to 302 healthy participants. Subjects were from both genders, ranging in age from 17 to 85 years (mean 50.6 ± 15.9 years) and in education from 1 to 20 years (mean 11.3 ± 3.7 years). Participants were grouped by age: 17-34 years old, 34-49 years old, 50-64 years old, and 65-85 years old. Pearson's Correlation analysis showed a significant association between RAVLT performance and both age and education (p < .001), but not between RAVLT performance and gender. Two-way analysis of variance revealed significant effects of age on all RAVLT measurements and significant effects of years of education on all measurements, with the exception of recognition. The present data indicate that participant age and education significantly influence performance on the RAVLT.